Futuristic and sophisticated garment for disable people futuristic and sophisticated garment for disable people “Titanium Spirit” / Koe Wei Loon and Fatin Nabilah Abdullah - Koe, Wei Loon; Abdullah, Fatin Nabilah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
The adaptive or multifunction garment in the category of smart casual wear for disable people and normal people which design to helps disable reduce the difficulties and time consuming to wear clothes besides less option on fashionable garment suit to their size. The advantage is, it is can be wear by disable and normal people which people don't know where is the special openings to counter their problems. In addition, it can be used suit to their disabilities or cover piece when they use wheelchair, sleep, or while they want to change the cloth. The fabric used will be comfortable and odourless such synthetic cotton, PD Interlock Jersey, PD Drill Korea Mix and PD Suiting. This multifunction and adaptive garment have secret opening at certain place which helps the user enjoy, easy wearing, comfort, less time consuming and be an independent person. Our aim is to provide solutions and reduce problems facing by disable people. We will produce product suit to their problem, starts from fabric selection that have special opening by using buttons, Velcro, zipper, string or special folds where it is particularly benefits well the janitor. We have high commitment to support this community by our product while makes them feel motivated on their lacknesses like resistant, confident, courage, eager and many more besides offering attractive fashion.